2011
DOI: 10.1039/c1cp22856k
|View full text |Cite
|
Sign up to set email alerts
|

A novel tungsten trioxide (WO3)/ITO porous nanocomposite for enhanced photo-catalytic water splitting

Abstract: Hybrid nanocomposite films of ITO-coated, self-assembled porous nanostructures of tungsten trioxide (WO(3)) were fabricated using electrochemical anodization and sputtering. The morphology and chemical nature of the porous nanostructures were studied by Scanning Electron Microscopy (SEM) and X-ray Photoelectron Spectroscopy (XPS), respectively. The photoelectrochemical (PEC) properties of WO(3) porous nanostructures were studied in various alkaline electrolytes and compared with those of titania nanotubes. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
(30 reference statements)
1
33
0
Order By: Relevance
“…[66] They found that in the multi-composite BiVO 4 /SnO 2 /WO 3 layers on the photoanode, the photocurrent at 1.23 V (vs. RHE) in 0.1 m carbonate electrolyte solution was more than 2.4 times higher than that in sul- Figure 17. [66] Ishihara et al, [6] found that the chemical nature of electrolytes played a crucial role in the efficient operation and energy conversion of a solar PEC cell. The inset represents the corresponding energy diagram for an n-type semiconductor and a metal as photoanode and photocathode, respectively.…”
Section: Evaluation Methods For Energy Conversion Efficiency Of Womentioning
confidence: 99%
See 2 more Smart Citations
“…[66] They found that in the multi-composite BiVO 4 /SnO 2 /WO 3 layers on the photoanode, the photocurrent at 1.23 V (vs. RHE) in 0.1 m carbonate electrolyte solution was more than 2.4 times higher than that in sul- Figure 17. [66] Ishihara et al, [6] found that the chemical nature of electrolytes played a crucial role in the efficient operation and energy conversion of a solar PEC cell. The inset represents the corresponding energy diagram for an n-type semiconductor and a metal as photoanode and photocathode, respectively.…”
Section: Evaluation Methods For Energy Conversion Efficiency Of Womentioning
confidence: 99%
“…Schematic representation of a PEC device for H 2 and O 2 evolution. [6] Hill and Choi [46] studied the various effects of different anions and cations contained in an electrolyte solution on the photocurrent conversion efficiency (Table 4). E F indicates the Fermi energy level.…”
Section: Evaluation Methods For Energy Conversion Efficiency Of Womentioning
confidence: 99%
See 1 more Smart Citation
“…The photocurrent response induced by the TiSi 2 ‐coating of the titania nanotubes is shown in Figure 5 (a) as a function of applied voltage vs. Ag/AgCl. An alkaline electrolyte containing a mixture of NaOH and KOH [0.5 M NaOH+0.3 m KOH+10 % ( v / v ) ethylene glycol+DI water] was used for the study, and the recipe was chosen based on the findings presented in our previous study 25. In that investigation, we discussed the fact that both titania nanotubes and porous tungsten nanostructures show the highest plateau‐photocurrent density (PPCD) for the electrolyte containing a mixture of NaOH and KOH.…”
Section: Resultsmentioning
confidence: 99%
“…The bandgap of this material is more suitable than TiO 2 (E g ≈ 3.2 eV) from the solar light application point of view. Indeed, unlike TiO 2 that absorbs only in the UV region of the solar spectrum, WO 3 can absorb wavelenght up to 500 nm [34]. Apart from its bandgap, WO 3 has many interesting features for technological applications.…”
Section: Womentioning
confidence: 99%